A field guide to succulents : colors, shapes and characteristics for over 200 amazing varieties - Matsuyama, Misa (Tuttle Publishing, 2023)
"A Field Guide to Succulents introduces you to over 200 popular succulent and cacti species including many you've never seen before! Each chapter serves as an illustrated field guide that covers the characteristics and needs of a particular succulent family, then zooms in to show you their attributes in detail and from angles that let you truly see what makes these varieties different from one another"--